Catalogue of statistical materials of developing countries 1983 - Insitite of developing economics (Tokyo : Institute of developing economics, 1983)
This 10th edition deals with the collection of the statistical reports from various China institute to form a rich data information management for developing countries.
asm; 05/03/19
Loans
Keywords: Statistics; Statistical services; Developing countries